Makna Pupuh Pucung ‘Bibi Anu’ Pengiring Ritual Nelu Bulanin Masyarakat Hindu Bali - I Komang Sulatra; Desak Putu Eka Pratiwi (Fakultas Bahasa Asing (FBA) Universitas Mahasaraswati Denpasar, 2024)
This research aims to determine the symbolic meaning of pupuh pucung entitled 'Bibi Anu' which is used as an accompaniment to nelu bulanin rituals. The data were taken from a video of the Nelu Bulanin ceremony from YouTube with the address https://www.youtube.com/watch?v=TTNtDppLjc0. The data were collected by applying the observation method through watching the video, transcribing the lyrics, reading, and note-taking the words or phrases that contain symbolic meaning. There were five stanzas of pupuh pucung used as data sources. This research used a qualitative approach. The analysis was carried out by applying the cultural-linguistic theory proposed by Palmer (1996). This research shows that the lyrics of 'Bibi Anu' use linguistic units like words and phrases with symbolic meaning as a means of expressing the beliefs of Balinese Hindu society. This research has proven that Pupuh Pucung ‘Bibi Anu’ not only accompanies the ritual but is an inseparable part of the ritual itself because the lyrics contain belief values as an inseparable part of Balinese culture.